Between the adversarial and the inquisitorial trial - Kamarudin, Abdul Rani (LexisNexis, 2007)
This article discusses and deliberates the nature of the adversarial trial in a criminal proceeding based on both the Malaysian Criminal Procedure Code (Revised Act 593/1999) (the CPC') and its replica, ie the Syariah Criminal Procedure (State of Selangor) Enactment 2003 (the State Syariah CPC'). The Criminal Procedure Code is based on the Common Law tradition. The French Civil Law tradition which is notable for its inquisitorial system is also considered to give a more balanced perspective to the discussion and to compare it with the common law tradition by highlighting the relevant provisions under both the CPC and the Shariah CPC relating to investigation and trial. It is then possible to ascertain whether justice is substantially seen to be done to both the opposing parties under both legal traditions. In other words, in a criminal proceeding, whether the adversarial mode of trial under the Common Law tradition is compatible with Islamic Law. This article also enlightens readers how the different legal traditions operate, and the importance of the need to be doubly careful in doing a complete overhaul/revamp of the existing mode of trial and in being too eager to throw aside a particular legal system that has been proved effective.